Aluminium content of foods originating from aluminium-containing food additives. Issue 3 (2nd July 2016) - Ogimoto, Mami; Suzuki, Kumi; Haneishi, Nahoko; Kikuchi, Yuu; Takanashi, Mayu; Tomioka, Naoko; Uematsu, Yoko; Monma, Kimio
ABSTRACT: Aluminium (Al) levels of 90 food samples were investigated. Nineteen samples contained Al levels exceeding the tolerable weekly intake (TWI) for young children [body weight (bw): 16 kg] when consuming two servings/week. These samples were purchased multiple times at specific intervals and were evaluated for Al levels. Al was detected in 27 of the 90 samples at levels ranging from 0.01 (limit of quantitation) to 1.06 mg/g. Of these, the Al intake levels in two samples (cookie and scone mix, 1.3 and 2 mg/kg bw/week, respectively) exceeded the TWI as established by European Food Safety Authority, although the level in the scone mix was equivalent to the provisional TWI (PTWI) as established by Joint Food and Agriculture Organization of the United Nations/World Health Organization Expert Committee on Food Additives. The Al levels markedly decreased in 14 of the 19 samples with initially high Al levels. These results indicated reductions in the Al levels to below the PTWI limits in all but two previously identified food samples.